Leadership-as-spiritual practice: a practical pneumatology of leadership in the Church of England - Bennet, HJ (2024)
My thesis investigates leadership discourse of the Church of England. I want to uncover how God is portrayed in discourse to discern what doctrine of God is having shaping effect on practice. Is there an underlying theological deficit in discourse that is affecting leadership practice? If so, how might discourse be repaired? The context for this research is a reforming programme which includes discussions about decision making and how the church is led. Previous criticisms focus on managerialism and the importation of organizational leadership language, while theologians note a lack of pneumatological engagement. My view is there is a dialectical relation between discourse and practice; discourse is meaning-making shaping social practice, which offers warrant to interrogate that discourse further. Located in practical theology, the methodology follows a Search-Encounter-Transformation arc. In my search phase, chapters 1-5, I question how ecclesial leadership discourse ‘speaks’ of God. ‘How is He named?’ Through content analysis, I find the person of the Spirit is under-represented as subject in leadership texts. In the encounter phase, chapters 6-8, via inter-disciplinary conversation, I explore how to repair this bias in discourse. I turn to systematic theology, to ecclesial practice, and the as-practice paradigm found in secular leadership studies. In chapter 9, I offer a synthesizing approach, a new ideational formation for discourse: leadership-as-spiritual practice. Leadership-as-spiritual practice is non-entitative and processual. Leadership emerges from mutual co-constructing conversation, and interaction of members of the Body of Christ with one another, and the Holy Spirit. This ideation reconceives leadership in such a way that an account of the Holy Spirit can be given in discourse thereby shaping practices around a more complete doctrine of God, thus enabling ecclesial leading to be better resourced pneumatologically.